THE PROMOTION OF BUMIAYU CITY THROUGH THE IMPLEMENTATION OF ILLUSTRATION OF LOCAL CULTURE ELEMENTS ON â€œBUMIAYU BEAUTY OF JAVAâ€ T-SHIRTS - Oktafiani, Dwi (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
The purpose of this project is to produce 10 illustrations that will be applied to the brand